2005
DOI: 10.1212/01.wnl.0000188907.97339.76
|View full text |Cite
|
Sign up to set email alerts
|

Elevated IL-6 and TNF-α levels in patients with ALS: Inflammation or hypoxia?

Abstract: Abnormal levels of interleukin (IL)-6 were described in patients with ALS, related to an inflammatory process. The authors compared IL-6 and tumor necrosis factor alpha (TNF-alpha) levels in CSF and sera from 10 hypoxemics and 10 normoxemics patients with ALS to those of 10 hypoxemics and 10 normoxemics neurologic controls. The same pattern exists in patients with ALS and controls: the highest levels are found in hypoxic conditions and undetectable levels are found in normoxemic conditions. Elevated IL-6 level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 10 publications
(10 reference statements)
6
89
0
10
Order By: Relevance
“…A recent study has also shown a positive correlation between CSF and serum interferon (IFN)-γ levels and both correlated with disease progression but not with ALSFRS-R scores [57]. Levels of interleukin (IL)-6 also correlated with hypoxic severity [54], suggesting that cytokine levels are dependent on oxygenation, which highlights a link between hypoxia and inflammation in ALS.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%
“…A recent study has also shown a positive correlation between CSF and serum interferon (IFN)-γ levels and both correlated with disease progression but not with ALSFRS-R scores [57]. Levels of interleukin (IL)-6 also correlated with hypoxic severity [54], suggesting that cytokine levels are dependent on oxygenation, which highlights a link between hypoxia and inflammation in ALS.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%
“…TGF-1 concentrations in the serum and CSF of ALS patients did not differ from controls, but TGF-1 serum concentration was significantly higher in ALS patients at the terminal clinical status (Ilzecka et al, 2002). Higher amount of IL-6 has been found in sera and CSF from sporadic ALS patients and it has been related to hypoxemia severity rather than pathological condition (Moreau et al, 2005). Plasma concentration of TNF-, TNF-R1 and TNF-R2 and their time course during disease progression were studied in ALS patients in order to assess the TNF- system implication in ALS pathogenesis.…”
Section: Cytokinesmentioning
confidence: 85%
“…In our study, cytokine concentrations were not markedly increased in plasma from mSOD1 mice, except for CXCL1 (KC). Rare studies have reported an increase of inflammatory cytokines in plasma from patients with ALS [22,[45][46][47][48]. To our knowledge, CXCL1 (KC) has never been measured in mSOD1 mice.…”
Section: Promising Effect Of Il-6 Blockade On Inflammation Statusmentioning
confidence: 98%